“Horizontal Peace” in Ukraine Simplified - Lars Hilse (Policy Perspectives)
This paper examines the complex nature of the Russo-Ukrainian conflict, arguing that its resolution requires a ‘horizontal peace’ approach rather than traditional vertical boundaries. The paper begins by analyzing Putin’s psychological profile, characterizing him as dominance-seeking with strategic patience and calculated aggression. Further, the paper traces the conflict’s origins to promises made during the fall of the Berlin Wall, particularly James Baker’s assurance that North Atlantic Treaty Organization (NATO) would not expand ‘one inch eastward’ beyond East Germany. It also critically examines the controversial role of the AZOV Brigade, acknowledging its neo-Nazi foundations while noting its evolution. The paper suggests that the conflict stems from competing interests: Russia’s cultural and security concerns versus Ukraine’s economic interests in the resource-rich Donbas region, estimated to contain mineral reserves worth over USD 15 trillion. The paper proposes a solution involving a horizontal division of interests—allowing Ukraine and the West access to subterranean resources while permitting the people of Eastern Ukraine cultural self-governance through a Compact of Free Association model similar to arrangements between the United States (US) and certain Pacific Island nations. The paper concludes that lasting peace requires acknowledging both the economic motivations of Ukraine and the cultural concerns of Eastern Ukrainians who have for centuries identified more closely with Russia.